Spatial and temporal patterns of disease burden attributable to high BMI in Belt and Road Initiative countries, 1990-2019 - Yaxin Xu; Qizhe Wang; Tao Yu; Yan Han; Wei Dai; Sunfang Jiang; Xiaopan Li (Cambridge University Press, 2024)
Abstract Objective: This study aimed to analyse the spatial and temporal patterns of disease burden attributed to high BMI (DB-hBMI) from 1990 to 2019 in Belt and Road Initiative (BRI) countries, in light of increasing hBMI prevalence worldwide. Design: The study was a secondary analysis of Global Burden of Disease 2019 (GBD 2019) that analysed (using Joinpoint regression analysis) numbers and the age-standardised rate of mortality and disability-adjusted life years (DALY) of hBMI-induced diseases and their trends from 1990 to 2019 and in the final decade. Setting: GBD 2019 study data for BRI countries were categorised by country, age, gender and disease. Participants: GBD 2019 data were used to analyse DB-hBMI in BRI countries. Results: In 2019, China, India and Russia reported the highest mortality and DALY among BRI countries. From 1990 to 2019, the age-standardised DALY increased in Southeast Asia and South Asia, whereas many European countries saw declines. Notably, Bangladesh, Nepal and Vietnam showed the steepest increases, with average annual percentage change (AAPC) values of 4·42 %, 4·19 % and 4·28 %, respectively (all P < 0·05). In contrast, Israel, Slovenia and Poland experienced significant reductions, with AAPC values of -1·70 %, -1·63 % and -1·58 %, respectively (all P < 0·05). The most rapid increases among males were seen in Vietnam, Nepal and Bangladesh, while Jordan, Poland and Slovenia recorded the fastest declines among females. Across most BRI countries, the burden of diabetes and kidney diseases related to hBMI showed a significant uptrend. Conclusion: DB-hBMI varies significantly by region, age, gender and disease type across BRI countries. It can pose a substantial threat to public health.